2009
DOI: 10.1186/1750-9378-4-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cervical cytology abnormalities and human papillomavirus in women infected with the human immunodeficiency virus

Abstract: Introduction: The human papillomavirus (HPV) is the major etiologic agent in the development of cervical cancer and its natural history of infection is altered in persons infected with the human immunodeficiency virus (HIV). The prevalence of HPV infection and cervical dysplasia in the HIV sero-positive females in the Bahamas is not known. Finding out the prevalence would allow for the establishment of protocols to optimize total care of this population and help prevent morbidity and mortality related to cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
5
14
1
Order By: Relevance
“…19 In the presence of high-risk HPV subtypes, cytological abnormalities may be present in up to 44% of HIV-infected women. 20 In the present study, the HIV-infected women had their first sexual intercourse at an earlier age, a higher number of sexual partners and a higher prevalence of STDs. Nevertheless, in the multivariate analysis, HIV infection remained independently associated with CIN.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…19 In the presence of high-risk HPV subtypes, cytological abnormalities may be present in up to 44% of HIV-infected women. 20 In the present study, the HIV-infected women had their first sexual intercourse at an earlier age, a higher number of sexual partners and a higher prevalence of STDs. Nevertheless, in the multivariate analysis, HIV infection remained independently associated with CIN.…”
Section: Discussionmentioning
confidence: 84%
“…Antiretroviral treatment reduces the risk of recurrence of cervical lesions, probably by restoring or preserving immune function. 19,20 Levi et al observed that 31% of the patients with fewer than 200 cells/ µl had abnormal cervical smears, in contrast with 13% of those with counts higher than 200 cells/µl. 5 In the present study, no relationship was observed between immunosuppression and lesion severity.…”
Section: Discussionmentioning
confidence: 99%
“…A striking observation of our study was that over half of the patients presenting cervical cytology abnormalities had HSILs or cervical cancer, comprising an overall prevalence of HSILs or cervical cancer of 21%. As far as we know, this is twice the rates described in different geographic populations of HIV-infected women (Dames et al 2009). We do not know the reasons for this discrepancy in relation to other studies.…”
Section: Discussionmentioning
confidence: 58%
“…We do not know the reasons for this discrepancy in relation to other studies. High-risk HPV types in HIV-infected women have been correlated with lower CD4 + T-cell counts (Dames et al 2009), but such a correlation was not feasible in our study because the CD4 measurements in our study were performed at 34 weeks of gestation, when most patients were already being treated with antiretrovirals. Further studies are ongoing to determine the risk factors for such rapid evolution of HPV infection in our study setting.…”
Section: Discussionmentioning
confidence: 93%
“…Cancer advocacy is very limited in Africa due to the intense focus on infectious diseases, in Africa for the past six decades. Ironically, the growing increase in cancer in Africa is thought to be a possible complication of long-term HIV infection, both in low-resource countries and in resource-rich countries [2,3]. Several reports point to the fact that long-term HIV infection may also predispose an individual to infectious disease-related cancers e.g.…”
Section: Introductionmentioning
confidence: 99%